Jammin’ the Blues: Experiencing the “Good Life” - Debrot, Ruth A. (Frontiers in Psychology, 2021)
The purpose of this study was to examine the characteristics, attitudes, and perceptions of older musicians who participated regularly in a local blues jam. Six core dimensions of eudaimonic well-being and their conceptual foundations provided a framework for examining the way that music-making contributes to subjective well-being during the lifespan of an individual. The following research questions guided this investigation: (1) In what ways do biographical factors and engagement with music influence the lives of older adult blues/rock musicians who participate in a local blues jam? (2) What implications for subjective well-being with regard to music learning might be used to inform music education practices? Interviews and observations over a 2-month period provided data for understanding how lived experiences impacted personal well-being, and musical growth and development over time. Findings suggested that eudaimonic well-being is the result of active engagement in human activities that are goal-directed and purposeful, and a good life involves the self-realization of individual dispositions and talents over a lifetime. Implications for music education include individualized pedagogical approaches that encourage learners to discover a sense of well-being in and through music.